Talking Head-based L2 Pronunciation Training: Impact on Achievement Emotions, Cognitive Load, and Their Relationships with Learning Performance. Issue 16 (1st October 2020) - Peng, Xiaolan; Chen, Hui; Wang, Lan; Tian, Feng; Wang, Hongan
ABSTRACT: Second language (L2) pronunciation training has been a worldwide task. Although computer technology makes it possible to develop a talking head to teach pronunciation like a real language teacher, little is known about how a talking head may act on L2 learners' emotional and cognitive learning process. We investigate L2 learners' achievement emotions, cognitive load, and pronunciation learning performance in a computer-assisted pronunciation training (CAPT) system embedded with four conditions: audio only (AU), a human face (HF), a 3D talking head with front view (3Df), and a 3D talking head with both front and profile views (3D). Results showed that, with learning time went on, participants' perceived anxiety, boredom, and pride increased while shame and hopelessness decreased and enjoyment kept stable. With 3D, participants' anxiety increased the most and boredom increased the least. Moreover, 3D group also perceived the highest germane load and got the highest pronunciation learning performance. Furthermore, anxiety and shame correlated with learning performance positively while boredom correlated with it negatively; enjoyment and pride correlated positively with performance on Mandarin tones. These findings significantly contribute to the efforts to design or select virtual characters for computer-aided language learning (CALL) and also provide a valuable reference to study achievement emotions in HCI systems.